Regulation of RIG-I Activation by K63-Linked Polyubiquitination - Okamoto, Masaaki; Kouwaki, Takahisa; Fukushima, Yoshimi; Oshiumi, Hiroyuki (Frontiers in Immunology, 2018)
RIG-I is a pattern recognition receptor and recognizes cytoplasmic viral double-stranded RNA (dsRNA). Influenza A virus, hepatitis C virus and several other pathogenic viruses are mainly recognized by RIG-I, resulting in the activation of the innate immune responses. The protein comprises N-terminal two caspase activation and recruitment domains (2CARDs), and an RNA helicase domain, and the C-terminal domain (CTD). The CTD recognizes 5’-triphosphate viral dsRNA. After recognition of viral dsRNA, the protein harbors K63-linked polyubiquitination essential for RIG-I activation. First, it was reported that TRIM25 ubiquitin ligase delivered K63-linked polyubiquitin moiety to the 2CARDs. The polyubiquitin chain stabilizes a structure called the 2CARD tetramer, in which four 2CARDs assemble and make a core that promotes the aggregation of the MAVS protein on mitochondria. MAVS aggregation then triggers the signal to induce the innate immune responses. However, subsequent studies have reported that Riplet, MEX3C, and TRIM4 ubiquitin ligases are also involved in K63-linked polyubiquitination and the activation of RIG-I. MEX3C and TRIM4 mediates polyubiquitination of the 2CARDs. In contrast, Riplet ubiquitinates the CTD. The physiological significance of each ubiquitin ligases has been shown by knockout and knockdown studies, but there appears to be contradictory to evidence reported in the literature. In this review, we summarize recent findings related to K63-linked polyubiquitination and propose a model that could reconcile current contradictory theories. We also discuss the physiological significance of the ubiquitin ligases in the immune system against viral infection.